Reflections of the Cult of the Holy Virgin Mary in Konstantinas Sirvydas’s Punktai sakymų - Rutkovska, Kristina (Senoji Lietuvos literatūra, 2020)
Based on exhaustive textual analysis of Konstantinas Sirvydas’s Punktai sakymų, the aim of the article is to show the picture of the Holy Virgin Mary created in the postil. A review of the period’s overall context of devotion to the Virgin Mary facilitates the understanding of Sirvydas’s religious views and their connection with the Jesuit-recognised and widely disseminated cult of the Virgin Mary, as well as his personal contribution to the spread of this cult. In Sirvydas’s postil, the picture of Mary is closely linked to the figure of Christ, while the dogmatic divine motherhood and Inoculate Conception remain at the centre. Sirvydas uses ascetic references to Mary, avoids elevated descriptions, and upholds the tradition of names of the Holy Scriptures because the Bible is the foundation of his sermons that is in line with the recommendations of Jesuit orations on moral and didactic issues. The sermons do not refer to the human and carnal picture of Mary. Most often, Sirvydas mentions only her spiritual qualities. Of special importance is the fact that Mary is attributed such qualities as the ability to think of supernatural phenomena, to perceive them and to be surprised by them, and to be aware of her own mission and role. In this context, her right to choose freely, which she has from the very beginning, is of great significance. Sirvydas speaks clearly and openly not so much of Mary’s submission to God’s will as of her own free will. Thus, in Sirvydas’s sermons the Virgin Mary arises as a free and sensitive individual contemplating and reflecting on the mysteries of birth and salvation. Her distinctive spirituality grows and develops gradually and includes not only her concern for Christ before and after his birth, but for the whole redeemed humankind. This becomes evident in the chapters where Mary arises as the symbol of the Church: she is given the gifts of reign and judgement, becomes the light of the world, and is loving, faithful, and devoted. Not only does Mary become a symbol of motherhood and chastity, but she is also the symbol of freely chosen true faith. When Sirvydas speaks of the free Mother of God, he simultaneously sees the ordinary human and envelops him or her in spiritual care; he extols positive qualities of the individual and opens the path to faith and holiness to everyone. To us, Sirvydas’s attention to the figure of the Virgin Mary not only reveals his theological views but also opens wider horizons of his worldview: his outlook on the human and society, moral foundations, and nurturing of a free spirit and free will.